First-principles calculations to investigate band gap of cubic BaThO3 with systematic isotropic external static pressure and its impact on structural, elastic, mechanical, anisotropic, electronic and optical properties. (October 2022) - Awais, M.; Zeba, I.; Gillani, S.S.A.; Shakil, M.; Rizwan, Muhammad
Abstract: The motive of this study is to offer a comprehensive evaluation of the structural, elastic, mechanical, anisotropic, electrical and optical characteristics of BaThO3 under the pressure range of 0 GPa–113 GPa. There is no phase transformation and the structure remains cubic but a diminishment in lattice parameters is observed. The material is found to be mechanically stable, inflexible, rigid and has high resistance to shear stress by computing the various elastic and mechanical (bulk modulus, shear modulus and young's modulus) parameters. The Pugh/Frantsevich ratios, Cauchy pressure, Poisson's ratio, and the Kleinman's parameter have proved the ductility, metallic bond nature and high-pressure endurance of the material. Distinctive anisotropy factors are engaged to verify that a compound is anisotropic. When the electronic band structure (BS) is taken into consideration, a change from wide band gap semiconductor (3.174eV) to narrow band gap semiconductor (1.832eV) and eventually metal (0eV) is seen. The total density of states (TDOS), the partial density of states (PDOS) and elemental partial density of states (EPDOS) have all been estimated in order to investigate the electronic BS. To enforce the relevance of this material, the real ε 1 (ω) and imaginary ε 2 (ω) dielectric functions, absorption I (ω), refractive index n (ω), extinction coefficient k (ω), loss function L (ω), reflectivity R (ω) and real/imaginary conductivity have all been calculated. The static values of ε 1 (ω) and n (ω) increase with applied pressure. Since its absorption spectra are present in the UV range, this is the best material to utilize as a UV filter. Additionally, its high refractive index, absorption, reflectivity, and conductivity make it an excellent component in optoelectronic devices. Graphical abstract: Image 1 Highlights: No phase transition is observed and structure remains in cubic. Different elastic constants have validated the mechanical stability of material. Material is inflexible, rigid, resistant to shear stress, ductile, and has metallic bonding and high pressure endurance. BaThO3 is anisotropic and predicted by four different anisotropy factors. Semiconductor to metal transition occurred i.e. (3.174eV–0eV).